Mechanism of Activating the Proprioceptive NT-3/TrkC Signalling Pathway by Reverse Intervention for the Anterior Cruciate Ligament–Hamstring Reflex Arc with Electroacupuncture. (18th January 2018) - Zhang, Lei; Zeng, Yan; Qi, Ji; Guan, Taiyuan; Zhou, Xin; He, Yancheng; Wang, Guoyou; Fu, Shijie
Abstract : The anterior cruciate ligament (ACL) is an important structure maintaining stability of the knee joints. Deficits in physical stability and the proprioceptive capabilities of the knee joints are observed, when the ACL is damaged. Additionally, a unilateral ACL injury can affect bilateral knee proprioception; therefore, proprioception of the ACL may play a key role in stability. Electroacupuncture therapy has a definite effect nerve regeneration. In this study, cynomolgus monkeys were randomly divided into 4 groups: the model control group, intervention of the injured knee with electroacupuncture (IIKE) group, intervention of the bilateral knees with electroacupuncture (IBKE) group, and the blank control group. The unilateral ACL injury model was developed in IIKE and IBKE groups; acupuncture points around the knees underwent intervention similarly in the IIKE and IBKE groups. Then, mRNA and protein expressions of NT-3 and TrkC in the dorsal root ganglion and of growth-associated protein-43 in the ACL increased according to reverse-transcription quantitative polymerase chain reaction and Western blotting results. Decreased incubations and increased amplitudes were found for somatosensory-evoked potentials and motor nerve conduction velocity. The finding indicates that electroacupuncture may play an important role in the recovery of proprioception in the ACL by activating the NT-3/TrkC signalling pathway.